Histopathological Changes in Incisive Teeth of the Newborn Pups of Cadmium-Applied Female Rats during Pregnancy - Deveci,S¸enay (Sociedad Chilena de Anatomía, 2010)
Cadmium Chloride is a well known teratogen compared to other metals. Cadmium affects placental function, may cross the placental barrier and modify fetal development. In this study, 12 female wistar albino rats weighted between 180-200gr were used. They were divided into two groups as experimental and control groups each comprising 6 female animals. 2mg/kg/day cadmium chloride dissolved in 1ml isotonic solution were intravenously injected from tail vein of experimental rats during 17-21 days of pregnancy. At first day of birth, the total body weights of control and experimental newborn pups were taken. This study aims to evaluate morphologically the effects of cadmium chloride on the incisive teeth development of pups born to the cadmium-applied female rats during pregnancy.